NOTAS HISTÓRICAS SOBRE AS PRAGAS DO ALGODOEIRO NO NORDESTE NO FINAL DO SÉCULO XVIII SEGUNDO O NATURALISTA MANUEL ARRUDA DA CÂMARA (1766-1811) - Almeida, Argus Vasconcelos de; Oliveira, Marco Aurélio Paes de; Albuquerque, Auristela Correia de (Revista Nordestina de Zoologia, 2011)
It is objective of this work to study the insect pests of cotton described by the naturalist Manuel Arruda da Câmara (1766-1811) in the late eighteenth century. The naturalist settled in Pirauá in Paraíba State, where he established on the banks of the river Paraíba, a large farm, in which intensely cultivated cotton. As a result of their experience of cotton-grower in 1799, he published the book "Memory on the cultivation of cotton”, which constitutes a true historical treatise on the culture. Seven cotton pests were observed and described by the naturalist, terming them as “Broca” (root borer in cotton; Eutinobothrus brasilensis (Hamblenton, 1937) Coleoptera, Curculionidae), “Lagarta” (leafworm cotton; Alabama argillaceae (Huebner, 1818) Lepidoptera, Noctuidae); “Gafanhoto grande” (grasshopper; Tropidacris collaris (Stoll, 1813), Orthoptera; Romaleidae); “Gafanhoto camaleão volante” (katydid; Steirodon striolatus (Brunner, 1878), Orthoptera, Tettigoniidae; Phaneropterinae), “Gafanhoto de grandes joelhos” (katydid; Stilpnochlora marginella (Serville, 1825) Orthoptera, Tettigoniidae; Phaneropterinae), “Gafanhoto pigmeu” (katydid, Scudderia beckeri Piza, 1967, Orthoptera, Tettigoniidae; Phaneropterinae); “Percevejo Gossypiphagus” (cotton bug; Dysdercus sp., Heteroptera; Pyrrhocoridae). It appears the insect pests reported today by the naturalist has no speech as such and which at the time the current main pests of cotton in the Northeast of Brazil were not yet identified. You can also see that the very concept of pest insects has changed over time.